Use of desalinated reject water as a source of magnesium for phosphorus recovery - Fattah, Kazi Parvez (2013)
In this study, the formation potential of struvite has been assessed using synthetic centrate mixed with reject water of a local desalination plant. NH4H2PO4, MgCl2 .6H2O,and NH4Cl were mixed in specific concentrations to simulate centrate of a wastewater treatment plant coming from centrifuge of anaerobic digesters. Due to the lack of adequate magnesium in domestic wastewater, the prepared synthetic centrate was further mixed with the reject water of MED and RO units of the desalination plant since it is rich in magnesium which is required for formation of struvite. Significant removal of phosphorus was observed through precipitation of phosphorus compounds after stirring the samples in a batch reactor.